Coalbed Methane Potential of The Muara Enim Formation in The South Sumatera Basin as a Source of Natural Gas - Yulfi Zetra; Burhan, R Y Perry; Shindy Eka Fittriani; Muhamad Nur Khozin; Zjahra Vianita Nugrahaeni; Rizka Berliana Putri; Husnul Rohma, (Malaysian Journal of Science (MJS), 2025)
Identification of aromatic hydrocarbon fraction by biomarker analysis was carried out to determine the geochemical characteristics of the coal samples from the Muara Enim formation in the South Sumatra basin for potential coalbed methane (CBM) exploration and production. Biomarker analysis using gas chromatography-mass spectrometry (GC-MS) shows the distribution of naphthalene, phenanthrene, and pentacyclic polyaromatic triterpenoid compound groups. The high abundance of 1,2,5- and 1,2,7- trimethylnaphthalene (TMN) compounds indicates that the organic matter in the coal samples mostly originated from higher Angiosperm plants that were deposited in a terrestrial and oxic environment. This terrestrial depositional environment was also indicated by the dominance of the 1,6- and 1,7- dimethylphenanthrene (DMP) compounds. The low maturity of the analyzed coal was indicated by the dominance of less stable isomers over more stable isomers. The identification of 2- and 1- methylphenanthrene (MP) biomarkers that are associated with type II and type III kerogens in relatively high abundance indicates that the analyzed coal samples tend to produce oil and gas. However, the lower abundance value of 2,7-dimethyl-1,2-(isopropylpenteno)-1,2,3,4-tetrahydrochrysene compared to 1,2,4a,9-tetramethyl-1,2,3,4,4a ,5,6,14b-octahydropicene indicates that the coal samples from the Muara Enim formation possess a higher potential to produce gas than oil. In addition, the high vitrinite content in the samples is related to type III kerogen, which shows that the coal is more gas-prone than oil-prone. The obtained methylphenanthrene index (MPI) value of 0.99 indicates moderate maturity of coal. These implicatons show that the analyzed coal can be exploited for its CBM gas content.